Government size and digital inequality in Indonesia - Yulianita, Anna; Subardin, Subardin; Zulfikri, Zulfikri (Journal of Governance and Accountability Studies, 2024)
Purpose: This study analyzed the impact of government size in the field of infrastructure on digital inequality in Indonesia. Method: This study uses panel data analysis with the CEM, FEM, and REM approaches using research samples from the Central Bureau of Statistics, Ministry of Finance, and International Telecommunication Union in Indonesia. Results: The results of this study indicate that government-sized infrastructure has a negative and significant effect on the ICT Index, while the square government-sized infrastructure/infrastructure expenditure optimization effect has a positive and significant impact on the ICT Index, and the implementation of the infrastructure budget supports digital equity; therefore, it is necessary to have an equal distribution of infrastructure in all corners in order to proportionally increase the allocation of the infrastructure budget. This means that the size of the government is still too small to equalize the increase in the ICT development index. Based on the government size threshold, the average for each province in Indonesia reached 68 percent. Limitations: This study was limited to the national level of each region in Indonesia. Contributions: This study aims to serve as a reference for government considerations in strategic policies related to infrastructure spending and issues of the technology change strategy.